2009
DOI: 10.1093/molehr/gap023
|View full text |Cite
|
Sign up to set email alerts
|

Comparative methylation profiles and telomerase biology of mouse multipotent adult germline stem cells and embryonic stem cells

Abstract: Recently, several groups described the isolation of mouse spermatogonial stem cells (SSCs) and their potential to develop to embryonic stem cell (ESC)-like cells, so-called multipotent germline stem cells (mGSCs). We were the first to derive such mGSCs from SSCs isolated from adult mouse testis and, therefore, called these mGSCs multipotent adult germline stem cells (maGSCs). Here, we comparatively analyzed gene-specific and global DNA methylation profiles as well as the telomerase biology of several maGSC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 51 publications
7
31
0
1
Order By: Relevance
“…The three mouse maGSC lines maGSC 129/Sv, maGSC C57BL/6 and maGSC Stra8 were derived from wild-type 129/Sv, wild-type C57BL/6 and transgenic Stra8-EGFP/Rosa26-LacZ-background mouse strains, respectively, without genetic selection and solely by morphological identification on the basis of formation of ESC-like colonies as previously described (Zechner et al, 2009). The corresponding male ESC lines ESC 129/Sv, ESC C57BL/6 and ESC Stra8 were isolated as described previously and used for comparison (Nagy et al, 1993;Zechner et al, 2009).…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…The three mouse maGSC lines maGSC 129/Sv, maGSC C57BL/6 and maGSC Stra8 were derived from wild-type 129/Sv, wild-type C57BL/6 and transgenic Stra8-EGFP/Rosa26-LacZ-background mouse strains, respectively, without genetic selection and solely by morphological identification on the basis of formation of ESC-like colonies as previously described (Zechner et al, 2009). The corresponding male ESC lines ESC 129/Sv, ESC C57BL/6 and ESC Stra8 were isolated as described previously and used for comparison (Nagy et al, 1993;Zechner et al, 2009).…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%
“…The corresponding male ESC lines ESC 129/Sv, ESC C57BL/6 and ESC Stra8 were isolated as described previously and used for comparison (Nagy et al, 1993;Zechner et al, 2009). The undifferentiated cell lines were maintained on Mitomycin Cinactivated mouse embryonic fibroblasts (MEFs) and cultured in standard ESC culture medium consisting of DMEM (PAN, Aidenbach, Germany) supplemented with 20% defined fetal bovine serum (PAN), 1% penicillin/streptomycin, 0.1 mM non-essential amino acids, 2 mM L-glutamine, 1 mM sodium pyruvate, 0.1 mM b-mercaptoethanol (all the above ingredients are from Gibco BRL, Eggenstein, Germany) and 1000 U/ml leukemia inhibitory factor (Chemicon, Temecula, CA, USA).…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was isolated from maGSC and male ESC lines by isopropanol precipitation and the promoter of Lrrc34 was analyzed by bisulfite pyrosequencing as described previously [13].…”
Section: Gene-specific Methylation Analysismentioning
confidence: 99%
“…Pluripotent stem cells were derived from adult mGSCs that not only could differentiate into a variety of cell types both in vivo and in vitro, but also showed germline transmission to the next generation when injected into blastocysts (Ko et al 2009). Moreover, mGSCs have pluripotency characteristics similar to ESCs such as telomerase activity, telomere length and hypomethylation of pluripotency marker genes (Zechner et al 2009) In recent years, several research groups reported methodologies for isolation and culture of human SSCs and also demonstrated that these cells were pluripotent/multipotent (Conrad et al 2008;Golestaneh et al 2009;Kossack et al 2009;Dym et al 2009;Izadyar et al 2011). SSCs isolated from human testicular tissues and cultured for a week or more spontaneously produced ESC-like small colonies, which were then transferred into ESC media and cultured for about 4 weeks to get sufficient numbers of ESC-like colonies and these ESC-like cells could then be differentiated into specific cell types.…”
Section: Spermatogonial Stem Cells Are Pluripotentmentioning
confidence: 99%